’Kosmopolitanisme Austronesian’ dan Indonesia sebagai Sistem Politik-Ekonomi - Eriko Aoki (Antropologi Indonesia, 2004)
Based on data from fieldwork in Flores, this article suggests an indigenous form of tolerance and suppleness as the model for a new form of multiculturalism in Indonesia. Many studies of nationalism have criticized the perspective that developing nation-states need 'strong nationalism. However, if we step out of this hegemonic preoccupation, we come to realize that the relevant question is not how Indonesia can keep its unity but on what conditions Indonesia can function well as a politico-economic system, keeping diverse areas incorporated in the post-modern and global contexts at present and in the future. In Flores, people have been traversing real and imagined borders since the time of the Austronesian migration and the age of Southeast Asian maritime commerce. Even after independence, Flores has had direct transnational linkage through the Catholic network and recently quite a few Catholic priests and candidates from Flores have been sent abroad. Due to the development of global capitalism, many people from mountainous areas in central Flores also go to Malaysia as low-paid labourers, and they accommodate well to the new situations. As illegal labourers, Florenese people develop social ties with the people whom they meet overseas. Even when they are arrested and forced to come home from Malaysia, they are never stigmatized in their home village. I would like to name tentatively this principle of social adaptability and political flexibility, which also orders life in Florenese villages, 'Austronesian cosmopolitanism'. I further suggest that this Austronesian principle of political flexibility could prove a useful model for the Indonesian nation-state as it struggles to adopt a new political model that prevents the escalation of retaliatory violence and allows the country to continue as a politico-economic unit.